The Wiley handbook of vocational education and training - Guile, David [Herausgeber]; Unwin, Lorna [Herausgeber] (Wiley Blackwell, 2019)
"The Wiley Handbook of Vocational Education and Training offers an in-depth guide to the theories, practices, and policies of vocational education and training (VET). With contributions from a panel of leading international scholars, the Handbook contains 27 authoritative essays from a wide range of disciplines. The contributors present an integrated analysis of the complex and dynamic field of VET. Drawing on the most recent research, thinking, and practice in the field, the book explores the key debates about the role of VET in the education and training systems of various nations. The Handbook reveals how expertise is developed in an age of considerable transformation in work processes, work organization, and occupational identities. The authors also examine many of the challenges of vocational education and training such as the impact of digital technologies on employment, the demand for (re)training in the context of extended working lives, the emergence of learning regions and skill ecosystems, and the professional development of vocational teachers and trainers." (Publisher, BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; T 1.5 International vergleichende Berufsbildungsforschung; 370; Berufsbildung; Berufsbildungsforschung; Berufsbildungspolitik; Berufsbildungssystem; Duales System; Digitalisierung; Bildungspersonal; Professionalisierung; Lernen am Arbeitsplatz; Lernumgebung; Typologie; Argentinien; Bundesrepublik Deutschland; China; Dänemark; Indien; Kanada; Niederlande; USA; Vereinigtes Königreich